Optimization of a Novel Mandelamide-Derived Pyrrolopyrimidine Series of PERK Inhibitors - Michael E. Stokes; Matthew D. Surman; Veronica Calvo; David Surguladze; An-Hu Li; Jennifer Gasparek; Matthew Betzenhauser; Guangyu Zhu; Hongwen Du; Alan C. Rigby; Mark J. Mulvihill (MDPI AG, 2022)
The protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) is one of three endoplasmic reticulum (ER) transmembrane sensors of the unfolded protein response (UPR) responsible for regulating protein synthesis and alleviating ER stress. PERK has been implicated in tumorigenesis, cancer cell survival as well metabolic diseases such as diabetes. The structure-based design and optimization of a novel mandelamide-derived pyrrolopyrimidine series of PERK inhibitors as described herein, resulted in the identification of compound 26, a potent, selective, and orally bioavailable compound suitable for interrogating PERK pathway biology in vitro and in vivo, with pharmacokinetics suitable for once-a-day oral dosing in mice.